2010
DOI: 10.1007/s12602-010-9047-2
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study Between the Antibacterial Effect of Nisin and Nisin-Loaded Chitosan/Alginate Nanoparticles on the Growth of Staphylococcus aureus in Raw and Pasteurized Milk Samples

Abstract: The aim of this study was to evaluate the antibacterial effect of nisin-loaded chitosan/alginate nanoparticles as a novel antibacterial delivery vehicle. The nisin-loaded nanoparticles were prepared using colloidal dispersion of the chitosan/alginate polymers in the presence of nisin. After the preparation of the nisin-loaded nanoparticles, their physicochemical properties such as size, shape, and zeta potential of the formulations were studied using scanning electron microscope and nanosizer instruments, cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(66 citation statements)
references
References 20 publications
7
58
0
1
Order By: Relevance
“…The results of similar research had agreement with other researcher results (Slütter et al 2010;Witschi and Doelker 1998). Results also showed that from four concentrations 0.5 % due to electrostatic stability and charge, balance was stable and observable under microscope (Zohri et al 2010). In formulations 0.1, 0.2 and 1 % concentrations, nanoparticles were not formed or were not stable for observation under SEM.…”
Section: Microscopic Image Assessmentsupporting
confidence: 88%
See 2 more Smart Citations
“…The results of similar research had agreement with other researcher results (Slütter et al 2010;Witschi and Doelker 1998). Results also showed that from four concentrations 0.5 % due to electrostatic stability and charge, balance was stable and observable under microscope (Zohri et al 2010). In formulations 0.1, 0.2 and 1 % concentrations, nanoparticles were not formed or were not stable for observation under SEM.…”
Section: Microscopic Image Assessmentsupporting
confidence: 88%
“…The structure of the nanoparticles is compact and their stability/solubility is greatly dependent on the pH. Release of streptomycin is a pH-dependent factor with attention to the in vitro release results, about 90-95 % release, in the medium with pH of 7.4 (because this pH leads to the more positive charge of nisin and consequently, more partitioning of streptomycin into the release medium) (Zohri et al 2010). It was shown that the nanoparticles have the same level of antimicrobial activity as the free drug.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, compounds allowing synthesis of carriers in the nanoscale, innocuous for living organisms and with biodegrading traits are very good candidates. As pointed out previously, chitosan and alginate are ideal materials for this task, being already used in the food industry due to their lack of toxicity, biodegradability and edibility (Zohri et al, 2010;Azevedo et al, 2014).…”
Section: But the Room Is Too Bigmentioning
confidence: 99%
“…CS-TPP nanoparticles were synthesized using ionotropic gelation between positively charged amino groups of chitosan and negatively charged TPP, as reported previously by Krauland and Alonso [21]. Briefly, chitosan (0.1%), TPP (0.1%) and Nisin 10 mg/ml were prepared and filtered with 0.22-µm filter.…”
Section: A Preparation Of Chitosan Tripolyphosphate Nanoparticlesmentioning
confidence: 99%